2023
DOI: 10.3390/ijms24043081
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as a Tool for Regulating Molecular Mechanisms in Depression: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Depression is one of the main mental disorders. Pharmacological treatment of depression is often associated with delayed effects or insufficient efficacy. Consequently, there is a need to discover new therapeutic methods to cope with depression faster and more effectively. Several lines of evidence indicate that the use of probiotic therapy reduces depressive symptoms. Nonetheless, the exact mechanisms linking the gut microbiota and the central nervous system, as well as the potential mechanisms of action for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A novel strategy to repristinate the gastrointestinal flora is the administration of probiotics, which are good living and transient entities that affect different pathways. Consuming probiotics has been demonstrated to enhance the expression of brain-derived neurotrophic factor (BDNF), a growth factor essential for memory, brain plasticity, and neuronal health that is severely low in depressed people [15][16][17]. Specifically, probiotics promote gut eubiosis and prevent cognitive function decline by decreasing amyloid-Beta (Aβ) levels in the hippocampus, reducing neuroinflammation, and maintaining neuronal structural integrity and plasticity [18].…”
Section: Introductionmentioning
confidence: 99%
“…A novel strategy to repristinate the gastrointestinal flora is the administration of probiotics, which are good living and transient entities that affect different pathways. Consuming probiotics has been demonstrated to enhance the expression of brain-derived neurotrophic factor (BDNF), a growth factor essential for memory, brain plasticity, and neuronal health that is severely low in depressed people [15][16][17]. Specifically, probiotics promote gut eubiosis and prevent cognitive function decline by decreasing amyloid-Beta (Aβ) levels in the hippocampus, reducing neuroinflammation, and maintaining neuronal structural integrity and plasticity [18].…”
Section: Introductionmentioning
confidence: 99%
“…The review underscored the potential benefits of probiotics in managing depression and anxiety symptoms, particularly in individuals with concomitant somatic disorders. Also, complex interactions between the gut microbiota, immune response, and brain function were highlighted, providing information about prospective treatment options for mental health problems [ 33 ]. The effects of probiotics on the microbiota–gut–brain axis show potential as a complementary treatment for some psychiatric disorders, particularly depression.…”
Section: Discussionmentioning
confidence: 99%
“…Both human and rodent studies indicated that probiotics reduce chronic-psychological-stress-induced abnormal brain activity and related cognitive dysfunctions by lowering plasma CORT and adrenocorticotropic hormone levels, restoring hippocampal 5-HT and NE levels, and normalizing immunity with low plasma levels of TNF-α but high levels of IL-10, an anti-inflammatory cytokine [ 171 , 172 , 173 ]. Several probiotics, as psychobiotics, for example, Bifidobacterium and Lactobacillus , deliver mental health benefits with neurobehavioral effects, which have been used in humans for improving cognitive function and for preventing and treating patients with behavioral impairment in neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease, and in diseases with neuropsychiatric disorders, such as anxiety, depression, and impulsively and compulsively disrupted social behavior [ 75 , 77 , 78 , 79 , 83 , 84 ]. Based on findings, targeting the gut microbiota has been recognized as a novel therapeutic option for patients with neuropsychiatric disorders [ 63 , 73 , 74 ].…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%
“…Targeting the intestinal microbiota with the goal of restoring its balance has been recognized as a novel therapeutic option for patients with neuropsychiatric disorders [ 72 , 73 , 74 ]. Several probiotics, as psychobiotics, such as Bifidobacterium and Lactobacillus , which can benefit mental health, have been used for preventing and treating patients with behavioral impairment, such as anxiety, depression, and impulsively and compulsively disrupted social behavior, via regulating the MGB, MGI, or both axes [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. However, the use of purified probiotics benefits has shown mixed results, with several weaknesses including transient beneficial effects, requiring continuous administration over time due to the host’s resident microbial populations and “colonization resistance” [ 85 ].…”
Section: Introductionmentioning
confidence: 99%